An Approach to the Spanish Consumer’s Perception of the Sensory Quality of Environmentally Friendly Seabass - Juan Benito Calanche Morales; Ana Tomás-Vidal; Edilson Ronny Cusiyunca Phoco; Silvia Martínez-Llorens; Pedro L. Marquina; Miguel Jover-Cerdá; Pedro Roncalés; José Antonio Beltrán (Foods, 2021)
Seabass is one of the leading aquaculture species in Europe. Sensory analysis is essential for new product development. This research focused on establishing and differentiating the opinion of consumers about seabass quality obtained with organic feeding. Fish were fed for 196 days with four treatments (a control diet with 30% fishmeal and three diets with different levels of fishmeal supplemented with organic vegetable ingredients: 25%, 30% and 35%). Experimental diets were compared with commercial samples from the retail industry that were considered as “adequate quality for fish”. Two sensory analyses were carried out, check-all-that-apply (CATA) to obtain feedback on consumers’ characterization towards a different type of fish evaluated and projective mapping (PM) to measure the similarity among a set of products and establish a comparison between results provided by both methods. According to the CATA results, white color, softness, meaty taste and juicy texture were considered relevant attributes, also showing a good relationship with an adequate cooked fish description. A penalty analysis confirmed that the previous characteristics were considered essential while fibrous was an undesirable attribute. The projective mapping showed a similar sensory configuration to the CATA, corroborating these findings that showed that commercial fish were placed in a position away from the rest of the treatments, and the organic diet with a higher level of fishmeal (35%) was the most distant from the control diet.